Learning the Qur'an with the Qalifa Method in Heterogeneous Groups Based on Learning Recommendations - Hanafi, Yusuf; Pahlevi, Andreas Syah; Fauzan, Moh.; Agus Prohimi, Afwan Hariri; Gunawan, Ari; Syafruddin, Afis Baghiz (EDUTEC : Journal of Education And Technology, 2023)
Quranic learning should ideally use a learning method that has certain guidelines and is carried out consistently. However, in certain cases a Quranic teacher faces special conditions and requires different treatment. The study groups that are handled have characteristics that vary between groups and internally the Quranic study group is very open to the possibility of being heterogeneous. However, currently in a place or group studying the Qur'an only uses one learning method so that it cannot provide opportunities for students to choose a learning method that suits their learning style. The purpose of this study is to analyze existing Quranic learning methods, provide recommendations to students for learning methods that are in accordance with their learning styles, streamline Quranic learning based on personalized learning. The method used in this study is Design Thinking Proccess. Based on the development research procedures that have been presented, there are 5 procedural steps of research based on design thinking. This research is very important to do considering that studying the Qur'an well is a priority for Muslims as a guide for living in the world.